Antimalarial evaluation of alkyl-linked bis-thiadiazine derivatives in murine model infected with two Plasmodium strains - Katherine Stefania Loachamin Gualotuña; Lilian M. Spencer; Hortensia Maria Rodriguez Cabrera; Renata Abigail Montero Calderón; Beatriz Pernía; Julieta Coro; Margarita Suarez; Francisco Javier Tingo Jacome; Zully J. Rodriguez Parra; Jose Manuel Lozano; Jesús Cortés Vecino (International Association of Physical Chemists (IAPC), 2023)
Background and Purpose: Plasmodium falciparum and P. vivax are responsible for most malaria cases in humans in the African Region and the Americas; these parasites have developed resistance to classic antimalarial drugs. On the other hand, previous investigations of the alkyl-linked bis tetrahydro-(2H)-1,3,5-thiadiazine-2-thione (bis-THTT) derivatives compounds show satisfactory results against protozoan parasites such as Trypanosoma cruzi, Trypanosoma vaginalis, Trypanosoma brucei rhodesiense and Leishmania donovani. Therefore, it is possible to see some effect of bis-THTT derivatives on other protozoan parasites, such as Plasmodium. Experimental Approach: This study aimed to perform an in vivo biological evaluation of bis-THTT (JH1 to JH6) derivatives compounds as possible anti-malaria drugs in BALB/c mice infected with Plasmodium berghei ANKA and Plasmodium yoelii 17XL strains. In this work, we evaluated the compounds as potential antimalarial drugs in BALB/c mice infected with Plasmodium strains. Key Results: For each compound, we assess the percentages of parasitemia by smears from tail blood and the humoral response by indirect ELISA test using each compound as an antigen. We also evaluated the B lymphocyte response and the cytotoxicity of the bis-THTT derivatives compounds with MTT cell proliferation assays. Conclusions: Our results show that the bis-THTT derivatives JH2 and JH4 presented effective parasitemia control in mice infected with P. berghei; JH5 and JH6 compounds have similar infection control results as chloroquine in mice infected P. yoelii strain. The evaluation of bis-THTT derivatives compounds in a model of BALB/c mice infected with P. berghei and P. yoelii allowed us to conclude that some of them have an antimalarial effect; however, none of the tested compounds exceeded the efficiency of chloroquine.